PENGARUH DEBIT AIR TERHADAP? PUTARAN?TURBIN?DAN?DAYA?OUTPUT? YANG?DIHASILKAN?PROTOTYPE PLTMH?DENGAN?TURBIN?KAPLAN - Ravinda Ariestya Pamungkas; I Wayan Arta Wijaya; I Gusti Ngurah Janardana (Program Studi Teknik Elektro UNUD, 2021)
Kaplan turbine is suitable turbine to use in the place that have small water fall (head)but need big water discharge. The problem from this turbine is the turbine need high waterdischarge to test the related parameters but it is too difficult to do because the water dischargeis not constant in the river. Based on the problems described, it is necessary to make a hydropower plant prototype using a Kaplan turbine with a laboratory scale so that it can obtainmaximum output result on a micro hydro power plant. The Method of analysis used is bycalculating the rimary data obtained. Prototype testing in this study uses water discharge thatvaries including 9 liter/s, 10 liter/s, 12 liter/s, 14 liter/s and 16 liter/s. The maximum outputobtained is when the water discharge is 16 liter/s which produces a turbine rotation of 228,3 rpmbefore the generator is coupled and 172,5 rpm after the generator is coupled, the generatorrotation is 902,5 rom, the generator voltage is 9,07 Volts, the generator current is 0,56Amperes, generator power is 5,09 Watt, torque is 0,28 Nm, and the efficiency occurs 1,62%.Based on the result of the study, the maximum output obtained is from the water discharge 16liter/s which is the biggest water discharge because an increase in the value of water dischargewill cause the micro hydro power plant performance to increase.